Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Klinik Pratama Rawat Inap El’rapha - Fani Febriyanti; Rosento Rosento (Journal of Management and Creative Business, 2024)
This research aims to determine the influence of work motivation and work environment on employee performance at the El'Rapha Inpatient Pratama Clinic. The sampling method used was a saturated sample. The sample in this study was 39 respondents. The data collection techniques used were observation and questionnaires in the form of statements. Using the multiple linear regression analysis method, and the data was processed using SPSS version 20. Based on the research results, partial hypothesis test results were obtained, namely T count 4.509 > T table 2.028 with a significant value of 0.000 < 0.05, so it can be concluded that work motivation has a partial effect on Employee performance, while the work environment variable obtained T count 2.678 > T table 2.028 with a significant value of 0.011 < 0.05, it can be concluded that the work environment has a partial effect on employee performance. The F test results obtained F count 51.669 > 3.259 and a significance value of 0.000 < 0.05, so it can be concluded that the variables of work motivation and work environment together (simultaneously) influence the performance of the El'Rapha Inpatient Pratama Clinic employees.